2010
DOI: 10.1002/hep.23935
|View full text |Cite
|
Sign up to set email alerts
|

A protective role for CD154 in hepatic steatosis in mice

Abstract: Inflammation and lipid metabolism pathways are linked, and deregulation of this interface may be critical in hepatic steatosis. The importance of the dialog between inflammatory signaling pathways and the unfolded protein response (UPR) in metabolism has been underlined. Herein, we studied the role of CD154, a key mediator of inflammation, in hepatic steatosis. To this end, Balb/c mice, wild-type or deficient in CD154 (CD154KO), were fed a diet rich in olive oil. In vitro, the effect of CD154 was studied on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
21
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 67 publications
8
21
1
Order By: Relevance
“…35,36 We found that in CD40L Ϫ/Ϫ mice, liver steatosis and NASH were strongly reduced, as were the expression levels of genes involved in glycolysis, fatty acid synthesis, and fat uptake. Contrary to our results, Villeneuve et al 37 found that CD40L was protective against the development of steatosis after administration of olive oil. However, the different dietary stresses that are used in the 2 models may be accountable for this difference.…”
Section: Weeks Of Hfd) a Clear Reduction In The Cd4contrasting
confidence: 99%
“…35,36 We found that in CD40L Ϫ/Ϫ mice, liver steatosis and NASH were strongly reduced, as were the expression levels of genes involved in glycolysis, fatty acid synthesis, and fat uptake. Contrary to our results, Villeneuve et al 37 found that CD40L was protective against the development of steatosis after administration of olive oil. However, the different dietary stresses that are used in the 2 models may be accountable for this difference.…”
Section: Weeks Of Hfd) a Clear Reduction In The Cd4contrasting
confidence: 99%
“…CD40 Ϫ/Ϫ mice develop hepatic steatosis and increased de novo lipogenesis in the liver. Recent literature has implicated CD40L as a protective factor against hepatic steatosis (43,46), which has a strong association with insulin resistance (29). Since we found impaired systemic insulin sensitivity in CD40…”
Section: Cd40supporting
confidence: 59%
“…In fact, the CD40-CD40L axis has recently been implicated in the pathogenic complications of obesity (32,43,46). However, various research groups have reported conflicting roles of CD40L in diet-induced obesity in mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tunicamycin (TM), a bacterial nucleoside antibiotic, can induce pharmacologic ER stress and stimulate unfolded and misfolded protein accumulation in ER. Numerous documents demonstrated that TM challenge could increase gene expression of GRP78 and Chop, as ER stress markers (10,36). Other studies also revealed that ER stress induction by hemocystein and TM led to hepatic steatosis in in vitro and in vivo models (24,36).…”
mentioning
confidence: 97%